A Survey of Students’ Satisfaction with Selected Academic Libraries in Kwara State - Oludipe , J. T. (International Journal of Educational Management, 2022)
The study investigated students’ satisfaction with selected Nigerian academic libraries. It specifically examined the inter-library loan services in academic libraries and the extent to which users made use of computer in their search for information in academic libraries. Survey method was used to collect data. Data were analyzed by means of frequency counts and simple percentage. The study among others revealed that library guides and catalogues played significant roles in the proper use of library materials. Based on the findings, it was recommended that academic libraries should embark on inter-library co-operation. Similarly, there should be more emphasis on library instruction and orientation programmes in order to encourage better library use. Finally academic libraries should improve their automation system and make more computers available for students’ use.